2005
DOI: 10.1007/s10208-004-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithmic Approach to Chain Recurrence

Abstract: ABSTRACT. In this paper we give a new definition of the chain recurrent set of a continuous map using finite spatial discretizations. This approach allows for an algorithmic construction of isolating blocks for Morse sets of Morse decompositions which approximate the chain recurrent set arbitrarily closely as well as discrete approximations of Conley's Lyapunov function. This is a natural framework in which to develop computational techniques for the analysis of qualitative dynamics including rigorous computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 14 publications
1
132
0
Order By: Relevance
“…In (Kalies et al, 2005;Ban and Kalies, 2006;Goullet et al, 2015) a computational approach to construct complete Lyapunov functions was considered. A discrete-time system was given by the time-T map and the phase space was subdivided into cells and the dynamics between them computed through an induced multivalued map using the computer package GAIO (Dellnitz et al, 2001).…”
Section: Complete Lyapunov Functionsmentioning
confidence: 99%
“…In (Kalies et al, 2005;Ban and Kalies, 2006;Goullet et al, 2015) a computational approach to construct complete Lyapunov functions was considered. A discrete-time system was given by the time-T map and the phase space was subdivided into cells and the dynamics between them computed through an induced multivalued map using the computer package GAIO (Dellnitz et al, 2001).…”
Section: Complete Lyapunov Functionsmentioning
confidence: 99%
“…Norton [26] even suggested that this characterization should be referred to as the Fundamental Theorem of Dynamical Systems. In [21], Kalies, Mischaikow and VanderVorst present an algorithmic approach to construct approximations to complete Lyapunov functions for discrete dynamical systems. By considering the time-T map of a continuous system, this method can be used to find an approximation to a complete Lyapunov function for a con-tinuous dynamical system as well.…”
Section: Introductionmentioning
confidence: 99%
“…This theorem implies that there is no fundamental algebraic obstruction to identifying any finite collection of attractors via attracting neighborhoods, which are computable objects [10]. Another consequence is an alternative proof of the existence of a index filtration to that presented in [8].…”
Section: Throughout This Paper We Make the Following Assumptionmentioning
confidence: 87%
“…As is demonstrated in [10], given a finite discretization of X and finite approximation of ϕ, elements of ANbhd(ϕ) and RNbhd(ϕ) can be computed. Part of the motivation for this paper is our belief that useful extensions and proper analysis of these types of computational methods requires a greater understanding of the above mentioned algebraic structures.…”
Section: Throughout This Paper We Make the Following Assumptionmentioning
confidence: 99%